2020
DOI: 10.1002/rcs.2189
|View full text |Cite
|
Sign up to set email alerts
|

New technology‐based assistive techniques in total knee arthroplasty: A Bayesian network meta‐analysis and systematic review

Abstract: Background The radiological and clinical efficiency among robot‐assisted surgery (RAS), computer‐assisted navigation system (CAS) and conventional (CON) total knee arthroplasty (TKA) remains controversial. Methods Bayesian network meta‐analysis (NMA) and systematic review were performed to investigate radiological and clinical efficiency, respectively. The certainty of the evidence was evaluated using Grading of Recommendations, Assessment, Development and Evaluation and Confidence in the Evidence from Reviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Clark et al [22] retrospectively compared these two technologies in total knee arthroplasty, and found that RAS (52 patients) led to decreased navigation time, fewer femoral malalignment and shorter hospitalization length compared to CAS (29 patients). Our previous network meta-analysis also demonstrated the best mechanical axis restoration with RAS, followed by CAS, and nally the conventional technique in total knee arthroplasty [23].…”
Section: Discussionmentioning
confidence: 78%
“…Clark et al [22] retrospectively compared these two technologies in total knee arthroplasty, and found that RAS (52 patients) led to decreased navigation time, fewer femoral malalignment and shorter hospitalization length compared to CAS (29 patients). Our previous network meta-analysis also demonstrated the best mechanical axis restoration with RAS, followed by CAS, and nally the conventional technique in total knee arthroplasty [23].…”
Section: Discussionmentioning
confidence: 78%
“…With the need to enhance the accuracy of surgery, computer‐assisted surgery (CAS) has been continuously advancing in the domain of total knee arthroplasty (TKA) surgery 1–3 . CAS started a few decades ago as computed tomography (CT)‐based/imageless navigation surgery, and the technology developed into robotically assisted surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional manual method cannot fulfill the requirement of rKA‐TKA implementation as it requires higher accuracy for individualized alignment. The development of new techniques including patient specific instrumentation (PSI), navigation, and robotic surgery improved the surgical precision of TKA, 14 which may be applicable in rKA‐TKA. However, errors still existed in executing surgical plans with the use of new techniques 15,16 .…”
Section: Introductionmentioning
confidence: 99%